Editorial Vol.14(1) - Jha, Ashok Kumar (Dristikon: A Multidisciplinary Journal, 2024)
With great satisfaction, the Research Management Cell (RMC) of Mahendra Multiple Campus, Dharan, announces the successful publication of the annual multi-disciplinary peer-reviewed research journal named Dristikon, as vol. 14(1) includes the editorial peer-review process that almost all scholarly and research articles published in the journal go through before being published to meet the requirements of the peer-review process that UGC, Nepal, and international standards guide. The purpose of the peer review procedure is to guarantee that the legitimate article gets approved, the disorganized piece gets fixed up, and the invalid article gets turned down. The editorial board has approved the suggestions of the reviewer. A thorough double-blinded peer review process is applied to every paper submitted for publication to guarantee its quality before it is published. A research article’s main goal is to present new information backed by evidence, and all the authors’ statements should be carefully examined before publication. In other ways, ChatGPT has shown to be more beneficial. Its ability to generate more sophisticated sentences is greater than unedited ones. It can produce a revised paragraph in a matter of seconds, and it's now free for everyone to use. The accepted papers, which covered the particular subjects of Nepali, English, Sanskrit, Economics, Education, Science, and Management, were added to the issue after the necessary changes and adjustments from the review process. The journal carefully adheres to the requirements of the APA 7th edition and vehemently rejects any information that has been copied without proper citation, as determined by the iThenticate plagiarism detection program. The writer's thoughts are their own, and neither the editorial board nor the publisher endorses anything that is written in the articles. After they are published, all manuscripts belong to the publishing company. As the Dristikon continues to grow and thrive, we hope that readers' inspiration and support will do the same. Your feedback and recommendations for future developments are also welcome and will be considered. The articles in this publication were submitted by authors in both Roman and Devanagari alphabetical order and were received from both campus and other colleges and institutions. To improve the journal's qualitative content, intellectuals, readers, and observers are invited to submit articles and comments. We appreciate the insightful feedback and recommendations from the peer reviewers. The editorial board would like to express its sincere gratitude to everyone who has contributed to the research publications. Additionally, we would like to express our gratitude to Assoc. Prof. Chandra Kumar Rai, Campus Chief for his unwavering assistance with finances and administration of the production of this journal.